Profiling of Amino Acids and Their Derivatives Biogenic Amines Before and After Antipsychotic Treatment in First-Episode Psychosis - Leppik, Liisa; Kriisa, Kärt; Koido, Kati; Koch, Kadri; Kajalaid, Kärolin; Haring, Liina; Vasar, Eero; Zilmer, Mihkel (Frontiers in Psychiatry, 2018)
Schizophrenia (SCH) is a heterogeneous disorder, deriving from a potential multitude of etiopathogenetic factors. During the past few years there has been an increasing interest in the role of circulating amino acids (AAs) and biogenic amines (BAs) in the pathophysiology of SCH. In the present study, we aimed to provide an insight into the potential role of alterations in levels of AAs and BAs as well as examine their more specific metabolic shifts in relation to early stage of SCH. We measured 21 AAs and 17 BAs in serum samples of patients with first-episode psychosis (FEP) before and after 7-month antipsychotic treatment in comparison to control subjects (CSs). According to multivariate analysis, antipsychotic-naïve FEP patients had significantly higher levels of taurine and spermine, whereas values of proline (Pro), alpha-aminoadipic acid (alpha-AAA), kynurenine (Kyn), valine (Val), tyrosine (Tyr), citrulline (Citr), tryptophan (Trp), and histidine (His) were diminished compared to CSs. Increased levels of taurine and spermine, as well as reduced levels of alpha-AAA and Kyn probably reflect the compromised function of N-methyl-D-aspartate (NMDA) receptors in patients. The decreased levels of Pro (AA modulating the function of glutamate decarboxylase) likely reflect the imbalanced function of gamma-aminobutyric acid (GABA) system in the brain of FEP patients. The alterations in ratio between Tyr and phenylalanine (Phe) can be taken as a sign of compromised function of dopaminergic system. These metabolic shifts were reinstated by 7-month antipsychotic treatment. Metabolic profiles of serum can be regarded as important indicators to investigate clinical course of SCH and treatment response.